The approach to sexual violence against women in primary care: a literature review (Research, Society and Development, 2022)
Sexual violence is defined as any sexual act, attempt to obtain a sexual act, unwanted sexual comments or advances, or acts directed at sex trafficking. Although it is a reality in the general population, women are the ones who suffer the most from this type of aggression, in this context the WHO pointed out that 35% of them reported having suffered some type of abuse during their lives. Information on violence and care provided occurs through notification to the Notifiable Diseases Information System (SINAN), which develops and implements public policies to combat violence. Primary care (AB), as a gateway, plays an important role in the care of sexually assaulted women, minimizing the damage suffered. The objective of this study is to review through the scientific literature the importance of an integral approach to primary care for victims of sexual violence. AB in a case of sexual violence, the woman must not only offer emotional support, but also prevent future damage to that victim, from the reception, as well as offering screening tests for sexually transmitted infections, emergency contraception and abortion guidelines. legal if a pregnancy occurs. The support work offered by AB to women affected by the clear expression of gender inequality is undeniably essential in the country, where the numbers of reported cases of violence are alarming. Integrity care for those who come looking for help is of paramount importance to bring them together to face and add to public policies aimed at cases of aggression in its most varied forms.